2022
DOI: 10.1002/mnfr.202100669
|View full text |Cite
|
Sign up to set email alerts
|

Garcinia Cambogia Improves High‐Fat Diet‐Induced Glucose Imbalance by Enhancing Calcium/CaMKII/AMPK/GLUT4‐Mediated Glucose Uptake in Skeletal Muscle

Abstract: Scope: Garcinia cambogia (G. cambogia) is known to have antiobesity effects. In this study, the therapeutic effects of G. cambogia on glucose homeostasis in obesity-induced diabetes are explored and the underlying mechanisms are investigated. Methods and results: C2C12 myotubes are treated with G. cambogia; glucose uptake, intracellular Ca 2+ levels, and related alterations in signaling pathways are examined. High-fat diet (HFD)-fed mice are administered G. cambogia for 8 weeks; oral glucose tolerance is evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In this study, a 2 mM dose of napin-derived oligopeptides was used primarily to elucidate the possible mechanisms of their protective effects against IR and oxidative stress in the IR-HepG2 cells. Recent studies reported that glucose consumption has been tightly related to GLUT4 on the plasma membrane, and glucose fails to freely enter cells through the lipid bilayer structure of the plasma membrane without GLUT4. , Therefore, it is necessary to investigate whether oligopeptides significantly increase GLUT4 expression and translocation in vitro or in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a 2 mM dose of napin-derived oligopeptides was used primarily to elucidate the possible mechanisms of their protective effects against IR and oxidative stress in the IR-HepG2 cells. Recent studies reported that glucose consumption has been tightly related to GLUT4 on the plasma membrane, and glucose fails to freely enter cells through the lipid bilayer structure of the plasma membrane without GLUT4. , Therefore, it is necessary to investigate whether oligopeptides significantly increase GLUT4 expression and translocation in vitro or in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that insulin resistance is the central feature of pathogenesis of metabolic syndrome, obesity, and T2DM. [30,31] Insulin resistant mice often show abnormal glucose homeostasis. [32] Thus, a model of HFD-induced insulin resistant mice was applied to evaluate the effects of peptides VY and SFLLR on insulin resistance.…”
Section: Effect Of Peptides Vy and Sfllr Supplementation On Glucose I...mentioning
confidence: 99%
“…[32] Thus, a model of HFD-induced insulin resistant mice was applied to evaluate the effects of peptides VY and SFLLR on insulin resistance. As shown in Figure S1, Supporting Information, the body weight at week 7 and 8, and glucose level at different test time points (15,30,60,90, and 120 min) as well as areas under the curve (AUC) based on oral glucose tolerance test (OGTT) were significantly increased in HFD-fed mice compared with the normal chow diet-fed mice, suggesting that HFD-fed induced obesity, impaired glucose tolerance, and insulin resistance. After 8 weeks of peptide VY or SFLLR supplementation, the fasting blood glucose (FBG) was gradually improved (Figure 2A); in particular, the VY-H and SFLLR-H groups reduced FBG by 35.38% (p < 0.001) and 38.31% (p < 0.001), respectively, in comparison to the HFD group.…”
Section: Effect Of Peptides Vy and Sfllr Supplementation On Glucose I...mentioning
confidence: 99%
“…Morover, G . cambogia administration resulted in significant blood glucose-lowering effects . HCA has attracted attention in Garcinia among its many other bioactives owing to its antiobesity effect and various action mechanisms in obesity management.…”
Section: Introductionmentioning
confidence: 99%
“…24 Morover, G. cambogia administration resulted in significant blood glucose-lowering effects. 25 HCA has attracted attention in Garcinia among its many other bioactives owing to its antiobesity effect and various action mechanisms in obesity management. Chiefly, HCA is a competitive inhibitor of the ATP-citrate lyase enzyme that converts mitochondria-derived citrate into acetyl CoA, a precursor for both fatty acid and mevalonate synthesis pathways.…”
Section: ■ Introductionmentioning
confidence: 99%